(untitled) (INNOVATIVE ECONOMY, 2025)
Varyha D.O., Mytsenko V.I. THE REGIONAL CONTEXT OF THE INTEGRATION OF UKRAINIAN ENTERPRISES INTO GLOBAL INNOVATION ECOSYSTEMS Purpose. The aim of the article is to substantiate of the regional context of the integration of Ukrainian enterprises into global innovation ecosystems by identifying key institutional and economic prerequisites, defining the role of regional specialization and innovation infrastructure, as well and systematizing the pathways and tools for including enterprises in international innovation networks. Methodology of research. The methodological basis of the study consists of general scientific and specialized methods of cognition, in particular the systems approach, methods of logical generalization, comparative analysis, structural and functional analysis, as well as elements of regional and institutional approaches. Their application made it possible to reveal the interconnection between the internal innovation potential of enterprises and the regional conditions for their inclusion in global innovation networks, as well as to identify the influence of innovation infrastructure, human capital, clustering, digitalization, and intersectoral interaction on integration processes. Findings. It has been demonstrated that the integration of Ukrainian enterprises into global innovation ecosystems depends not only on the level of technological development of individual businesses, but also on the specific characteristics of the regional environment in which they operate. It is determined that the region acts as an intermediate but strategically important link between the enterprise’s local resources and global channels of innovation, investment, scientific-technological, and production cooperation. Originality. The theoretical understanding of the regional context of Ukrainian enterprises’ integration into global innovation spaces has been deepened, viewed as a multilevel process shaped by the interaction of intra-firm, regional, and foreign economic factors. The content of regional prerequisites for innovation integration has been clarified, and their significance as a basis for the inclusion of enterprises in global networks for the creation and commercialization of knowledge has been substantiated. Practical value. The obtained research results can be used in the formation of regional economic policy, innovation development strategies, entrepreneurship support programs, cluster initiatives, and tools for stimulating international innovation cooperation. Key words: regional development, corporate innovation, management, globalization challenges, regional innovation systems, innovation integration, controlling, innovation ecosystems, digitalization, competitiveness, efficiency.